Pre‐treatments enhance the therapeutic effects of mesenchymal stem cells in liver diseases - Hu, Chenxia; Wu, Zhongwen; Li, Lanjuan (Journal of cellular and molecular medicine, 2020)
Liver diseases caused by viral infection, alcohol abuse and metabolic disorders can progress to end‐stage liver failure, liver cirrhosis and liver cancer, which are a growing cause of death worldwide. Although liver transplantation and hepatocyte transplantation are useful strategies to promote liver regeneration, they are limited by scarce sources of organs and hepatocytes. Mesenchymal stem cells (MSCs) restore liver injury after hepatogenic differentiation and exert immunomodulatory, anti‐inflammatory, antifibrotic, antioxidative stress and antiapoptotic effects on liver cells in vivo. After isolation and culture in vitro, MSCs are faced with nutrient and oxygen deprivation, and external growth factors maintain MSC capacities for further applications. In addition, MSCs are placed in a harsh microenvironment, and anoikis and inflammation after transplantation in vivo significantly decrease their regenerative capacity. Pre‐treatment with chemical agents, hypoxia, an inflammatory microenvironment and gene modification can protect MSCs against injury, and pre‐treated MSCs show improved hepatogenic differentiation, homing capacity, survival and paracrine effects in vitro and in vivo in regard to attenuating liver injury. In this review, we mainly focus on pre‐treatments and the underlying mechanisms for improving the therapeutic effects of MSCs in various liver diseases. Thus, we provide evidence for the development of MSC‐based cell therapy to prevent acute or chronic liver injury. Mesenchymal stem cells have potential as a therapeutic to prolong the survival of patients with end‐stage liver diseases in the near future.